Sustainability Development Model of MSMEs Through Financial Literacy and Financial Inclusion - Riskianita, Winda; Pajri, Tiko; Tohir, Tohir; Firmansyah, Firmansyah; Hamsani, Hamsani (2023)
The role of Micro, Small and Medium Enterprises (MSMEs) plays an important role in the Indonesian economy, especially in improving the economy of the poor, reducing poverty and generating foreign exchange. The phenomenon that occurs in MSMEs in Bangka Belitung Province, MSME actors have weaknesses in financial literacy and financial inclusion. This study aims to produce a model for developing MSME sustainability so that it can be used as a reference by MSME actors in improving performance, sustainability, developing and maintaining their business. This study examines the culinary, handicraft, services, agribusiness and grocery stores using a quantitative approach. This research was conducted to find out whether financial literacy and financial inclusion actually affect the sustainability of MSMEs. Sampling was taken using the proportional sampling method and the samples were distributed using the Google form, measurements used a Likert scale of 5 scores and analyzed using the Smart Partial Least Square. This study shows that Financial Literacy and Financial Inclusion positively do not have a significant effect on MSME sustainability.